Design and application of the continuous positive airway pressure mask capable of preventing pressure injuries (一种防压疮面罩的设计与应用) - LIAO Juanjuan (廖娟娟); WU Yaqin (吴娅琴); TAN Xiaofei (谭小菲) (中西医结合护理, 2023)
Pressure injury is a common adverse event during the noninvasive mechanical ventilation therapy. This paper introduced the design and application of the continuous positive airway pressure mask which is capable of preventing device-related pressure injuries. (压疮是采用无创机械通气治疗的患者常见不良事件, 预防压疮是护理工作的重要内容。本研究介绍一款实用新型防压疮面罩的设计和使用方法, 其能够有效避免压疮和提高患者佩戴舒适度。)